Uma análise do perfil da inadimplência do crédito habitacional da Caixa Econômica Federal no Estado do Ceará - Lima, Marco César Aguiar (2008)
The problem of failing to carry out a contract that occurs in the housing financing in Brazil is a big drawback to the national development and therefore it does not reduce the lack of housing that affects the Brazilian population. The volume of housing credit is growing year after year specially after the banking institutions had to invest into the housing financing instead of investing into the financial market. Although these investments brought good revenues to the institutions these same investments did not bring any improvement to the financial indicators of Brazil such as jobs, number of houses financed, reduction of housing deficit among others. In this paper, an econometric model was used to explore the client profile in case of breaches of contracts according to some variables considered important in the study of the causes of a non-payment situation and some possible solutions. The data used in this model were collected from CEF – CAIXA ECONÔMICA FEDERAL considered the financial institution with the greatest participation into the housing financing and besides this CEF is the government main agent on the execution of social policies. Some of the results must be used as an alert the financial institutions that are in the market such as the growing number of housing units available in big cities, like in Fortaleza in Ceará, that could bring to a failing to carry out contracts. Among that the continuum of the reduction of interest rates and the extended time payments are some of facilities that are given to the fulfillment of a dream to many Brazilians- to buy their own house. Therefore it is necessary even more the use of instruments that could insure a better risk management to guarantee a return to the investments made and to continue the housing programs that are already in the market.